Effect of Marble Powder Mixed with Concrete on Mechanical Properties for Use as Concrete Roof Tiles - Saeyang, Nirat; Chanpichai, Nongluk (Journal of Science and Technology CRRU, 2024)
This research aims to study the physical properties of concrete roof tiles mixed with marble powder in various ratios, produced by molding the tiles with concrete containing a mixture of Portland cement type 1, sand, water, waterproofing solution and a substance that accelerates the formation of calcium chloride. with a percentage ratio of 21.73 : 59.78 : 16.30 : 1.53 : 0.66 and marble powder added in the ratio by mass of concrete and marble powder with a ratio by mass of 1:0, 0.9:0.1, 0.8:0.2, 0.7:0.3, 0.6:0.4 and 0.5:0.5 formed by mold size 33 x 42 x 1 centimeter. It was found that the appropriate amount of marble powder For mixing in concrete roof tiles, the ratio is 0.9:0.1. Tests have been carried out according to industrial standards, TIS 535-2013, and the test results following the requirements, with a transverse pressure value of 1,117.78 newtons, with a % of water absorption value was 9.68 each and the thermal conductivity is 0.02 W/m.K, under the standard for concrete roof tiles. The roof tiles from this research can be used as roofing material.